Analysing modelled nearshore wave climate variability and change as relevant to the traditional handline fishery of the South African South Coast - Lyttle, Casey Tara (Department of Environmental and Geographical Science, 2019)
The South Coast traditional handline fishing communities of South Africa are integrated into a complex ecosystem where human and natural components interact and overlap on many different spatial and temporal scales. The South Coast marine ecosystem, on which the fishers depend, already suffers from depleted fish stocks. The South Coast handline fishery is therefore vulnerable to added stresses such as those induced by climate change. While fishers have noted that deteriorating sea state and a declining number of sea days caused by shifts in wind patterns are affecting their livelihood, applicable scientific research and data on scales relevant to the fishers is insufficient. Insight into the complexities involved in climate change and local-scale responses of these highly integrated social-ecological system therefore remains sparse. While South Coast nearshore winds have been the subject of recent research, the wave climate aspect of the nearshore sea state has not. In a recent project conducted by the Department of Environmental Affairs and the Council for Scientific and Industrial Research, Simulating WAves Nearshore model outputs spanning 17 years (from 1997 to 2014) were produced for the South African coastline, including the South Coast. Wind (speed and direction) and swell (significant wave height, peak wave direction and period) outputs from the WaveWatch III model (provided by National Centre of Environmental Prediction, US) were used as boundary conditions. The present study uses these wave model outputs to conduct an investigation into the nearshore local-scale wave climate of four traditional handline fishing towns of the South Coast: Witsand, Still Bay, Gouritz and Mossel Bay. Results suggest that the shape and bathymetry of the coastal sites influence average significant wave height, peak wave directions, and seasonal variability of the approaching swell waves. This is due to the nearshore processes of refraction, bottom friction and sheltering by headlands from the approaching swell, driven by the offshore swell. Additionally, the presence of low peak period waves depended on the focussing of waves that were generated by easterly winds during summer (i.e., wind-waves, which are shorter period waves compared to swell) driven by the synoptic-scale winds. While summer afternoon waves remained higher than morning waves from 1997 to 2014, the significant wave height difference did not change over time; however, variability increased post-2006, particularly for sites more exposed to approaching swell. A regime shift in mean significant wave height was detected for 2006 across the South Coast, from lower to higher waves. The more exposed study sites showed a strong seasonality (higher waves during winter than summer), where the duration of summer conditions lengthened post-2006 during the period of higher significant wave heights. Significant wave height increased significantly from 1997 to 2014 across the South Coast. Since swell dominates across the South Coast, the observed regime shift (including interannual variability) and trend is likely to be attributed to offshore swell. The recent increase in wave height variability is in line with fishers observations where increase in climate variability has been observed. The increase in wave height is also in line with fishers' observations which state that the sea state has deteriorated, and sea days have decreased. Additionally, the lengthening duration of summer conditions in waves was also observed by fishers in terms of winds. This analysis of South Coast wave climate contributes to bridging the gap between the first hand observations of fishers and conclusions drawn from coarse resolution scientific data.